PENGGUNAAN METODE SIMULASI QUASI MONTE CARLO DENGAN BARISAN QUASI ACAK VAN DER COURPUT DALAM MENENTUKAN HARGA OPSI EROPA - Lita Wulandari Aeli; Dodi Devianto; Hazmira Yozza (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2022)
An option is a right by a person or institution to sell or buy an investment instrument at a certain price for a certain period. The point of view for way an option is exercised, there are two types of options known today, namely European options and American options. European options are characterized by option contracts that can only be exercised at the expiration date of the option. American options are indicated by option contracts that can be exercised at any time within the validity of the option contract. There are several methods that can be used in determining option prices, including the Black Scholes method which can be used to calculate the standard price of options. Monte Carlo simulation is a method that gives all possible values of a variable using the average as an estimator of its exact value. Quasi Monte Carlo simulation is an alternative to Monte Carlo simulation which uses quasi-random sequences instead of random numbers. In this article, the quasi-random sequence used is Van der Courput. Calculate option prices with Monte Carlo simulation and Quasi Monte Carlo simulation using MATLAB.